TEACHER PERCEPTION IN COMPUTER ASSISTED INSTRUCTION, ADOPTION FOR EDUCATION SUPPORT IN PUBLIC SECONDARY SCHOOLS IN KENYA - Molenje, Mary; Mukwa, Prof. Chris; Too,, Prof. J. (IJRDO- Journal of Educational Research, 2017)
Computers can provide a more flexible and effective ways of professional development forteachers to improve pre- and in-service, teachers training and connect teachers to the globalteachers community. The purpose of this study was to investigate the teacher perception incomputer assisted instruction, adoption for education support, in Kenyan secondary schools. Thestudy sought to address the following objectives; Find out the teachers’ attitude towards thecomputer use and to assess the perceived barriers towards computer instruction. The studyadopted the technology acceptance model (TAM) by Davis (1989) which expresses howtechnology is integrated into the instruction process. Other theories include, Theory of ReasonedAction (TRA) and Theory of Planned Behavior (TPB). A descriptive survey research design wasused. Stratified sampling was used to select One hundred and fifty schools; Purposive samplingwas used to select the Head teachers and Simple random sampling was used to select theteachers. A total representative sample of 414 respondents was used. Questionnaires andinterviews schedules were used as instruments for data collection. Internal consistency(Reliability) of the research instrument was ascertained using the test re test technique as well asCronbach's alpha of 0.75 and above. Data was coded and analyzed using Statistical Package forSocial Sciences (SPSS) Version 21.0 as well as STATA version 13.0.Descriptive statistics suchas frequencies, percentages and means was used to analyze the data. Data was presented in tablesand pie charts appropriately. The study would benefit teachers, school managers, curriculumplanners and policy makers, developers and implementers in coming up with the best integrationapproaches for the use of computers in teaching and learning in Kenyan secondary schools.